2005
DOI: 10.1162/1054746053967049
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation Practice for Upper-Limb Amputees Using Virtual Reality

Abstract: We developed a novel interface that gives upper-limb amputees a virtual hand that can manipulate objects in a challenging environment. The interface registers specific myokinetic activity of the residual limbs, and encodes the intended voluntary movements that are then actualized as virtual hand motions. The composite myokinetic interface-virtual reality (MKI-VR) system consists of an array of pressure sensors mounted in an arm sleeve, sensors of elbow-and shoulder-joint angles, a trained filter derived from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Although we report on only nondisabled subjects, the results may apply to the transradial amputee population, since previous studies have shown that the amplitude of single-finger volitions can by extracted via FMG [15,17]. Test conditions were limited to the arm and wrist in a fixed neutral position in the horizontal plane.…”
Section: Validity Of Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Although we report on only nondisabled subjects, the results may apply to the transradial amputee population, since previous studies have shown that the amplitude of single-finger volitions can by extracted via FMG [15,17]. Test conditions were limited to the arm and wrist in a fixed neutral position in the horizontal plane.…”
Section: Validity Of Studymentioning
confidence: 99%
“…The ability of FMG to resolve hand postures and individual finger motions has previously been demonstrated in transradial amputees, some of whom were >15 years postamputation and had relatively poor residua [14][15]17]. More recently, it has been shown that six different grip types can be classified with considerable accuracy when FMG is used to measure intact forearms [21].…”
Section: Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…Arm amputation level has a strong influence on the affected person's ability to perform ADLs, and compared to lower amputation levels, the compensatory strategies developed by transhumeral amputees to overcome the impairment involve significantly more the rest of the body, causing shoulder, back, and contralateral limb disorders [4]. Numerous studies have investigated alternatives to bi-electrodes myoelectric control, such as solutions based on ultrasound signal [5], myokinemetric signal [6], myokinetic signal [7], mechanomyographic signal [8], and residual limb motion [9], [10]. One possible and yet less explored solution relies on the use of residual limb motion and the knowledge of human upper limb motor control to design a more natural control strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Manfuladevi et.al. developed another VR training system to train artificial hand control for amputee [2].…”
Section: Introductionmentioning
confidence: 99%